Cognitive Enhancement using Meditation as Intervention - Narang, Mahak (My University, 2014)
Cognition refers to all the processes that organism uses to organize information. This includes cognitive abilities like memory, attention, language, visual and spatial processing, logic and reasoning, interpersonal and intrapersonal reasoning. It has been scientifically proved that cognitive abilities can be improved upon by certain interventions. Meditation is one of the methods with which we can enhance the cognitive ability of a person. There are several other methods by which cognitive enhancement can be done, like using odor, music, etc. EEG based improvements in cognitive abilities like attention and working memory using custom designed meditation is proposed. EEG records electrical activities from the scalp. Different parts of brain show different electrical activities during various mental processes. We focus on enhancing these cognitive abilities of brain. The study is divided into two parts. In first part activities of brain are recorded during various tasks related to attention and working memory. Similar tests are repeated after subjects are exposed to meditation as an intervention for 15 days for half an hour daily. For checking the level of enhancement various parameters of physiological signals are considered, like for attention alpha power and beta power are considered and for working memory alpha power and theta power are considered. The 5 subjects are made to do the same tasks after 15 days. Both the signals of pre and postinterventions are compared on account of these parameters. The post meditation results show enhancement in both attention as well as working memory. These enhancements are observed in the task performance scores as well as in the corresponding EEG frequency band powers.
Master of Engineering-EIC-Dissertation
Keywords: Cognition; Cognitive assessment; Cognitive Enhancement; Meditation; EEG; Power Spectrum Density; Alpha Theta Beta Power; Working Memory